Progress of fracture mapping technology based on CT three-dimensional reconstruction - Liu, Jichao; Zhang, Ziyan; Qu, Ji; Piao, Chengdong (Frontiers in Bioengineering and Biotechnology, 2024)
Fracture Mapping is a new technology developed in recent years. This technology visually representing the morphology of fractures by overlaying fracture lines from multiple fracture models onto a standard model through three-dimensional reconstruction. Fracture mapping has been widely used in acetabular fracture, proximal humerus fractures, Pilon fracture, tibial plateau fractures, and so on. This technology provides a new research method for the diagnosis, classification, treatment selection, internal fixation design, and statistical analysis of common fracture sites. In addition, the fracture map can also provide a theoretical basis for the establishment of a biomechanical standardized fracture model. Herein, we reviewed various methods and the most advanced techniques for fracture mapping, and to discuss the issues existing in fracture mapping techniques, which will help in designing future studies that are closer to the ideal. Moreover, we outlined the fracture morphology features of fractures in various parts of the body, and discuss the implications of these fracture mapping studies for fracture treatment, thereby providing reference for research and clinical decision-making on bone and joint injuries to improve patient prognosis.